Water scarcity and crop management: a global challenge - Dotaniya, M L; Meena, M D; Doutaniya, R K; Rai, P K; Dotaniya, C K (Indian Farming, 2022)
Freshwater availability is dwindling over the world as time passes. Agricultural crop production techniques require a lot of water to produce enough food grain to feed the world’s growing population Farmers must rely on low-quality water to maximize water potential which has a larger concentration of soluble salt as well as a significant amount of trace metal. Long-term use of poor quality water has a negative impact on soil health and crop productivity. With adequate treatment and moisture conservation measures, it is possible to better exploit the water potential of marginal grade water resources. In water-scarce settings, combining soil moisture methods with improved soil health management alternatives could boost food grain yield.